2015
DOI: 10.1177/0886260515614561
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Pathways Linking Childhood Maltreatment to Interpersonal Revictimization During Adolescence for Girls in the Child Welfare System

Abstract: This study compares the association of histories of childhood emotional, physical, and sexual abuse, and physical neglect with revictimization among adolescent girls, and investigates the role of posttraumatic stress and symptoms of depression as mediators. Participants were 234 girls aged 12 to 19 years, who have been involved with the child welfare system in a Midwestern urban area. Data were collected from baseline surveys of a trauma-focused group program to which the participants were referred. The majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…In line with previous studies, we showed that CTEs are associated with mental health, health, and well-being in adulthood independent of risk factors in adulthood. Consistent with previous studies (Ney, 1987 ; Martin et al, 2006 ; Norman et al, 2012 ; Dias et al, 2014 ; Spinazzola et al, 2014 ; Auslander et al, 2015 ; Friborg et al, 2015 ), psychological abuse in childhood was associated with a higher risk for being mentally unhealthy and unhealthy, as compared to physical abuse.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with previous studies, we showed that CTEs are associated with mental health, health, and well-being in adulthood independent of risk factors in adulthood. Consistent with previous studies (Ney, 1987 ; Martin et al, 2006 ; Norman et al, 2012 ; Dias et al, 2014 ; Spinazzola et al, 2014 ; Auslander et al, 2015 ; Friborg et al, 2015 ), psychological abuse in childhood was associated with a higher risk for being mentally unhealthy and unhealthy, as compared to physical abuse.…”
Section: Discussionsupporting
confidence: 86%
“…However, this approach assumes that each type of CTE has an equivalent weight, and that there is an additive effect, when in fact some CTEs may have a stronger effect than others, and there may not be any additive effect (Cohen et al, 1997 ; Martin et al, 2006 ; Schilling et al, 2008 ). For instance, previous studies have shown that psychological abuse has a greater negative effect on mental health and health in adulthood, as compared to physical abuse in childhood (Ney, 1987 ; Martin et al, 2006 ; Norman et al, 2012 ; Dias et al, 2014 ; Spinazzola et al, 2014 ; Auslander et al, 2015 ; Friborg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children who are maltreated are more likely to develop mental health problems such a depression, anxiety and substance use in young adulthood (Dion et al, 2016;Khan et al, 2015;Scott et al, 2012). Moreover, it has been determined that previous childhood maltreatment can lead to intrapersonal problems such as decreased self-esteem, as well as increased risk for re-victimization of abuse as an adult (Auslander et al, 2016;Widom, 2014). Due to the multiple negative consequences of childhood maltreatment, researchers are working to fully understand the effects that maltreatment has on the child's mental health and well-being.…”
mentioning
confidence: 98%
“…The extant revictimization literature almost exclusively focuses on sequelae of initial sexual abuse or assault episodes as contributing to risk for subsequent harm (for reviews see Arata, 2000; Classen et al, 2005; Messman-Moore & Long, 2003). For example, symptoms of depression, anxiety, and PTSD have been found to increase risk for revictimization in youth and adult samples (Auslander, Tlapek, Threlfall, Edmond, & Dunn, 2015; Cuevas, Finkelhor, Clifford, Ormrod, & Turner, 2010; McCart et al, 2012; Wolfe, Wekerle, Scott, Straatman, & Grasley, 2004). Maladaptive, abuse-related cognitions such as self-blame, loss of trust, and negative self-appraisals (Penning & Collings, 2014) stemming from initial abuse experiences, and health risk behaviors including substance and alcohol use, unprotected sex, prostitution, and having frequent sexual partners (Fergusson, Horwood, & Lynskey, 1997; Krahe, Scheinberger-Olwig, Waizenhofer, & Kolpin, 1999; Testa, Hoffman, & Livingston, 2010) also place individuals at heightened risk.…”
mentioning
confidence: 99%